Notch-mediated conversion of activated T cells into stem cell memory-like T cells for adoptive immunotherapy - Taisuke Kondo (Nature Portfolio, 2017)
Tumour-specific T cells can be expandedin vitroand adoptively transferred for therapy, but this strategy is limited by induction of short-lived T cell populations. Here the authors activate Notch signalling in cultured mouse or human T cells, resulting in the production of a long-lived stem cell memory T cell population that can fight tumours in mice.